Memory, catastrophe and utopia. About Adorno and literature - Escobar Moncada, Jairo (Estudios de Filosofía, 2004)
This essay intends to explore some of Adorno’s relations with literature, having as leitmotiv the concepts of memory, catastrophe, and utopia. Literature’s memory is rebellion against the veil of oblivion with which mass media and the spheres of power want to cover catastrophes, cruelties and lies lived by a society, and of it, contributes to keep utopia: the wish that society can be organized more justify. In the center of Adorno’s reflection on literature is the relation between the literary work and society, and the relations of the former, through form, with the latter How does the truth of a work of art entail? flow to think the relationship between work of art and society without giving way to sociologism? Does the work of art fulfill a cognitive role? Answering to this questions is the goal of this essay.